Cellular mechanisms of complex I-associated pathology. (26th November 2019) - Abramov, Andrey Y.; Angelova, Plamena R.
Abstract : Mitochondria control vitally important functions in cells, including energy production, cell signalling and regulation of cell death. Considering this, any alteration in mitochondrial metabolism would lead to cellular dysfunction and the development of a disease. A large proportion of disorders associated with mitochondria are induced by mutations or chemical inhibition of the mitochondrial complex I — the entry point to the electron transport chain. Subunits of the enzyme NADH: ubiquinone oxidoreductase, are encoded by both nuclear and mitochondrial DNA and mutations in these genes lead to cardio and muscular pathologies and diseases of the central nervous system. Despite such a clear involvement of complex I deficiency in numerous disorders, the molecular and cellular mechanisms leading to the development of pathology are not very clear. In this review, we summarise how lack of activity of complex I could differentially change mitochondrial and cellular functions and how these changes could lead to a pathology, following discrete routes.